An Overlooked Silica Source of the Modern Oceans: Are Sandy Beaches the Key? - Fabre, Sébastien; Jeandel, Catherine; Zambardi, Thomas; Roustan, Michel; Almar, Rafaël (Frontiers in Earth Science, 2019)
We consider the Si flux resulting from sand grain dissolution on beaches under the pressure of the intensive and continuous shaking by the waves, a potential source of oceanic DSi that is not currently considered. Today, DSi source and sink fluxes are balanced within large uncertainties, at ca. 10.4 ± 4.2 and 14.6 ± 7.8 × 1012 mol yr–1, respectively, underlining that some processes are not well constrained and possibly overlooked so far. To quantitatively explore this idea, we first realized an experimental dissolution of quartz grains in a stirred vessel designed to simulate the sediment orbital motion induced by the waves. These experiments lead to the calculation of a solid–liquid mass-transfer coefficient directly linked to the rotation speed of the shaker. This coefficient being itself related to the energy communicated to the liquid, we could apply the Nienow relationship to calculate a mass-transfer coefficient for beach sand exposed to 1 m height waves. Extrapolation of this value to the whole sandy beaches led us to conclude that this mechanism could be significant, shortening the calculated residence time of oceanic DSi by up to a factor 2.